2023
DOI: 10.3389/fmicb.2023.1068595
|View full text |Cite
|
Sign up to set email alerts
|

Archaea and their interactions with bacteria in a karst ecosystem

Abstract: Karst ecosystems are widely distributed around the world, accounting for 15–20% of the global land area. However, knowledge on microbial ecology of these systems does not match with their global importance. To close this knowledge gap, we sampled three niches including weathered rock, sediment, and drip water inside the Heshang Cave and three types of soils overlying the cave (forest soil, farmland soil, and pristine karst soil). All these samples were subjected to high-throughput sequencing of V4-V5 region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Candidatus_Nitrocosmicus also belongs to the phylum Crenarchaeota and is a genus in the family Nitrososphaeraceae. It has a strong aerobic ammonia oxidation biofunction and can oxidize high concentrations of ammonia [49,50]. As observed in both Figures 2b and 4a, the relative abundance of the genus Candidatus_Nitrocosmicus at XHS3 was significantly higher than that at the other sites, corresponding to the apparently high NO 3 − and NO 2 − concentrations at this site.…”
Section: Discussionmentioning
confidence: 73%
“…Candidatus_Nitrocosmicus also belongs to the phylum Crenarchaeota and is a genus in the family Nitrososphaeraceae. It has a strong aerobic ammonia oxidation biofunction and can oxidize high concentrations of ammonia [49,50]. As observed in both Figures 2b and 4a, the relative abundance of the genus Candidatus_Nitrocosmicus at XHS3 was significantly higher than that at the other sites, corresponding to the apparently high NO 3 − and NO 2 − concentrations at this site.…”
Section: Discussionmentioning
confidence: 73%
“…Methanomassiliicoccales has been reported to perform methyl-dependent hydrogenotrophic methanogenesis [53]. Cheng et al reported that Nitrosopumilaceae may play fundamental roles in obtaining energy under oligotrophic conditions and thus maintaining the stability of the cave ecosystem [54].…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Thaumarchaeota and Euryarchaeota in the bioaerosols of the three indoor environments was around 1% during both UP and OP, showing relatively higher levels than other regions. This observation might be associated with the unique karst geology of the Guilin area because these bacteria are usually detected in soil and water in karst areas [42,43]. ods of personnel activities; DOUP, the dormitory during periods of few personnel activities; DOOP, the dormitory during periods of personnel activities; CAUP, the canteen during periods of few personnel activities; CAOP, the canteen during periods of personnel activities.…”
Section: Bioaerosol Bacterial Community Structurementioning
confidence: 94%